1999
DOI: 10.1124/mol.56.6.1309
|View full text |Cite
|
Sign up to set email alerts
|

Murine Transgenic Cells Lacking DNA Topoisomerase IIβ Are Resistant to Acridines and Mitoxantrone: Analysis of Cytotoxicity and Cleavable Complex Formation

Abstract: Murine transgenic cell lines lacking DNA topoisomerase II (topo II)beta have been used to assess the importance of topo IIbeta as a drug target. Western blot analysis confirmed that the topo IIbeta -/- cell lines did not contain topo IIbeta protein. In addition, both the topo IIbeta +/+ and topo IIbeta -/- cell lines contained similar levels of topo IIalpha protein. The trapped in agarose DNA immunostaining assay (TARDIS) was used to detect topo IIalpha and beta cleavable complexes in topo IIbeta -/- and topo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
79
1
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(96 citation statements)
references
References 30 publications
14
79
1
2
Order By: Relevance
“…The most robust potentiation was observed with mitoxantrone and mAMSA, while marginal potentiation was obtained for etoposide and no significant effect was seen for doxorubicin or epirubicin. Cells lacking topoisomerase IIβ have previously been shown to be resistant to mitoxantrone and mAMSA, 28,29 indicating a significant role for this isozyme in the cytotoxicity of these drugs, whereas the degree of resistance to etoposide or doxorubicin in topoisomerase IIβ null cells was smaller. Similarly, we found the IC 50 for mitoxantrone in growth inhibition assays is five times higher in topoisomerase IIβ null Nalm-6 cells than in their wild type counterparts while the ratio is only 2.8 for etoposide (data not shown).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The most robust potentiation was observed with mitoxantrone and mAMSA, while marginal potentiation was obtained for etoposide and no significant effect was seen for doxorubicin or epirubicin. Cells lacking topoisomerase IIβ have previously been shown to be resistant to mitoxantrone and mAMSA, 28,29 indicating a significant role for this isozyme in the cytotoxicity of these drugs, whereas the degree of resistance to etoposide or doxorubicin in topoisomerase IIβ null cells was smaller. Similarly, we found the IC 50 for mitoxantrone in growth inhibition assays is five times higher in topoisomerase IIβ null Nalm-6 cells than in their wild type counterparts while the ratio is only 2.8 for etoposide (data not shown).…”
Section: Discussionmentioning
confidence: 89%
“…24 Recently, specific roles in transcription regulation and sperm chromatin remodelling have been uncovered for topoisomerase IIβ. [25][26][27] The topoisomerase IIα isoform is the major target for most clinically-relevant topoisomerase poisons including etoposide and epirubicin 12,28,29 although the -β isoform appears to contribute more for some topoisomerase poisons including mitoxantrone, mAMSA and XK469. [28][29][30] Several mechanisms could explain the sensitization of cells to topoisomerase poisons by HDAC inhibitors 13,15,31 but notably, it was recently reported that this potentiation is mediated specifically through topoisomerase IIβ.…”
Section: Histone Deacetylase Inhibition Redistributes Topoisomerase Imentioning
confidence: 99%
“…The HL-60 cell line and its mitoxantrone-resistant (TOP2-deficient) variant, HL-60͞MX2, were obtained from the American Type Culture Collection (17). The simian virus 40-transformed TOP2␤ knockout mouse embryo fibroblast cell line TOP2␤(Ϫ͞Ϫ) and its parental simian virus 40-transformed TOP2␤(ϩ͞ϩ) cell line were cultured under the same condition (18).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, two studies suggested that Top2␣, rather than Top2␤, was the determinant of cytotoxic effects of etoposide (27,28). Even more intriguingly, Azarova et al (27) suggested that Top2␤ may be responsible for the development of secondary malignancy associated with etoposide treatment.…”
Section: Dna Topoisomerase II (Top2)mentioning
confidence: 99%